The Translation of Politeness Strategies Associated with Power Relation in Pramoedyaâ€™s Cerita Calon Arang and The King, the Priest and the Witch - Darta, Deta Maria Sri (Journal of Language and Literature, 2018)
Translating is not as simple as changing a text form one language into another. It is more complicated, since it involves many aspects including linguistics and culture. Yet, translation is a helpfull aid when it comes to the International area. In literature, for example, a literary text owes a help from translation to be world wide acknowledged. This makes the duty of a translator becomes heavier, due to the burden of translating literary text that should be faithfull. This article gives example of the unfaithfull translation of a literary text from Indonesian into English, focusing on the translation of the politeness strategies found. The analysis showed that there are several politness strategies deleted or not translated, which made the translated text unfaithfull. While the translation strategies used resulted on different level of accuracy and acceptability.Â Keywords: literary text, politeness strategies, translation techniques, translation qualityÂ